Status of lean manufacturing practices and its influence on the adoption of industry 4.0 in the Malaysian furniture industry - Ratnasingam, Jegatheswaran; Zbieć, Marcin; Lim, Choon Liat; Ab Latib, Hazirah; Othman, Kamaruzaman; Amir, Mohd Afthar; Jegatheswaran, Natkuncaran (Warsaw University of Life Sciences, 2022)
Status of Lean Manufacturing Practices and Its Influence on the Adoption of Industry 4.0 in the Malaysian Furniture Industry. Lean Manufacturing practices is being promoted throughout the manufacturing industry in the country to boost industrial productivity. Therefore, a study was carried out to determine the level of adoption, benefits, and challenges faced by furniture manufacturers in adopting LM. Further, it was also evaluated if LM facilitated the transition towards Industry 4.0 adoption. The questionnaire-based survey involved 484 furniture manufacturers, of large-size and SMEs. The results found that the adoption of LM was prevalent among large-sized companies, and LM improved product quality and customer satisfaction, while reducing manufacturing lead time in the companies. The 5S method of work place organization, process mapping and waste reduction and elimination were the most common LM tools adopted by the companies. On the other hand, the major challenges encountered when implementing LM were lack of know-how, backsliding to old work ways, and resistance to adopt among the employees. The result also revealed that companies practicing LM also suggested that they were more prepared to adopt Industry 4.0 technologies, as the practice of LM has not only reduced waste on the production shopfloor, but also improved the information flow that is important for digital tools of Industry 4.0.